Atlas of Sustainable Development Goals 2017 : From World Development Indicators - World Bank (Washington, DC: World Bank, 2017)
The Atlas of Sustainable Development Goals 2017 uses maps, charts and analysis to illustrate, trends, challenges and measurement issues related to each of the 17 Sustainable Development Goals. The Atlas primarily draws on World Development Indicators (WDI) - the World Bank's compilation of internationally comparable statistics about global development and the quality of people's lives